Survival and Efficiency of Temperature Tolerant and Temperature Sensitive Strains of Rhizobium sp. (Acacia) under Temperature Stress Conditions - Rustagi, N.; Duhan, J.S.; Sharma, P.K. (Indian Journal of Agroforestry, 2020)
Out of 100 isolates of Rhizobium spp. nodulating A. nilotica two temperature tolerant Rhizobium spp. (Acacia) strain AC-2 and AC-6 with ability to grow at 45° C and 40° C respectively, were compared with a temperature sensitive Rhizobium sp. (Acacia) strain AC-11 for their survival, nodulation and nitrogen fixation (nitrogenase activity) at elevated temperature Survival of the temperature tolerant strains AC-2 and AC-6 was better at 40° C and 45° C than the temperature sensitive strain AC-11 in sterilized soil Nitrogenase activity in nodules formed by AC-2 and AC-6 on A. nilotica was more at 45° C and 40° C in comparison to nitrogenase activity in the nodules formed by AC-11. Seedlings inoculated with strains AC-2 showed 7-13% reduction in shoot dry weight up to 45° C whereas 34-36% reduction in shoot dry weight was observed with AC-6. Inoculation with temperature sensitive strain AC-11 also showed the similar trend (33-40%) as that of AC-6 strain.